Research on 5GtoB customized network based data offloading scheme - Yaping CAO; Ying SUN; Huixiao ZHANG (Dianxin kexue)
With the continuous evolution of 5G network, 5GtoB solution for industrial users is also more flexible.Data offloading can well meet the urgent needs of customers for data not leaving the park, local unloading, local support, low delay and so on.The demand background of data offloading capability in 5G network and the relevant principles of diversion technology were introduced.At the same time, combined with the actual deployment of operators' existing network, the application scenarios and technical implementation of two kinds of data offloading schemes based on multi data network name (DNN) and uplink classifier (UL CL) were expounded, and the advantages and limitations of different schemes were compared and analyzed.Finally, the feasibility of the scheme was verified by an actual case.